Prognostic significance of programmed death-1 (PD-1) and programmed death-ligand 1 (PD-L1) expression in uterine carcinosarcoma. (January 2020) - Kucukgoz Gulec, Umran; Kilic Bagir, Emine; Paydas, Semra; Guzel, Ahmet Baris; Gumurdulu, Derya; Vardar, Mehmet Ali
Abstract: Objective: The aim of this study was to evaluate the clinical and prognostic importance of programmed death-1 (PD-1) and/ or programmed death-ligand 1 (PD-L1) in uterine carcinosarcoma (UCS). Study Design: Formalin-fixed, paraffin-embedded tissue samples from 59 cases with UCS were analyzed. PD-1 and PD-L1 expressions in tumor tissue and microenvironment were detected by immunohistochemistry. Clinical and pathological characteristics including age, stage, initial symptom, surgical approach, myometrial invasion, lymphovascular space invasion (LVSI), lymph node invasion, adjuvant therapy, and survival were evaluated. The Kaplan-Meier and Cox proportional hazards models were used to compare the outcomes and prognostic factors. Results: PD-1 expression in tumor tissue and microenvironment was detected in 15 (25 %) and 18 (30 %) cases, respectively. PD-L1 expression in tumor tissue and microenvironment was detected in 15 (25 %) and 12 cases (20 %), respectively. PD-L1 expression in tumor was associated with longer survival and median survival was 38 and 15 months in cases with and without PD-L1 expressions, respectively (p = 0.019). Lymphovascular space invasion (LVSI) (p = 0.014), myometrial invasion (p = 0.008) and PD-L1 expression were found to be prognostic for UCS's. PD-L1 expression was found to be an independent good prognostic factor with Cox regression analysis (OR 3.9; 95 % CI: 1.4–11.0) for overall survival. Conclusion: PD-1 and/or PD-L1 expression are important due to their expressions in one fourth of the cases with UCS and PD-1/PD-L1 blockade may be a new avenue in UCS.